Multifunctional water-retaining agent adapting to acid soil and preparation method thereof

By using modified clay minerals and composite additives in water retention agents, the water absorption performance and stability in acidic soil environment are improved, the problem of low water absorption performance in acidic soil is solved, and the soil's water holding and fertilizer retention effect is achieved. Suitable for drought and soreness problems in the southern region.

CN119144338AActive Publication Date: 2024-12-17INST OF SOIL SCI CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411155881.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-17
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

The existing soil water retention agent has low water absorption performance in acidic soil environments and is complex in the process, making it difficult to effectively solve the problems of seasonal drought and sourness in the southern region.

Method used

Using a multifunctional water retention agent composed of chitosan, guar gum, acrylic acid, sodium polyphosphate, methylenebisacrylamide, ammonium persulfate and clay minerals, the modification treatment of clay minerals and the use of composite additives , improve the water absorption performance and stability of the water retention agent.

Benefits of technology

It significantly improves the water absorption performance of the water retention agent, enhances the soil's water holding capacity and fertilizer retention ability, can maintain moisture for a long time at high temperatures, adapt to the acidic soil environment, extends the water supply capacity, and improves the soil's pH and CEC.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144338A_ABST
    Figure CN119144338A_ABST
Patent Text Reader

Abstract

The invention discloses a multifunctional water-retaining agent adapted to acid soil and a preparation method thereof, and the multifunctional water-retaining agent is prepared from the following raw materials in parts by weight: 9-11 parts of a chitosan solution with the concentration of 0.019-0.021 g / mL, 9-11 parts of a sodium polyphosphate solution with the mass concentration of 0.5-1%, 24-25 parts of an acrylic acid solution with the neutralization degree of 80-85%, 9-11 parts of a guar gum solution with the concentration of 0.019-0.021 g / mL and the balance of water. The mass of the methylene bisacrylamide accounts for 0.01-0.03% of the total dry matter mass of the chitosan, the guar gum and the acrylic acid, the mass of the ammonium persulfate accounts for 0.25-0.35% of the total dry matter mass of the chitosan, the guar gum and the acrylic acid, and the clay mineral accounts for 10-12 parts; the preparation method comprises the following steps: S1, pre-preparation; S2, mixing; and S3, post-treatment. The prepared water-retaining agent not only can greatly improve the water absorption and water retention performance of the chitosan water-retaining agent, but also can reduce the acidity of acid soil and improve the CEC and fertilizer retention capacity of the soil, and is a multifunctional acid red and yellow soil conditioner.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soil admixtures, and in particular to a multifunctional water-retaining agent suitable for acidic soil and a preparation method thereof. Background Art

[0002] Water retainers, also known as super absorbents, are widely used in agriculture, medicine, textiles, construction and other fields because of their unique three-dimensional network structure and a large number of hydrophilic functional groups (carboxyl, amino, hydroxyl, etc.) attached to their polymer main chains. They can absorb and store dozens to nearly a hundred times of salt water or thousands of times of water. Water retainers are also gradually used for soil improvement. By improving soil structure, increasing soil water retention, retaining soil nutrients, reducing water evaporation and underground seepage, they can effectively alleviate soil drought and even fertilizer retention problems. They are important conditioners for regulating soil water, fertilizer, air and heat conditions. At present, the water retainers used in the market are mainly synthetic resin water retainers, which are mainly prepared using acrylic acid and acrylate as monomers. These water retainers have the advantages of high water absorption, strong salt resistance and good composite effect. However, most of these water retainers are non-biodegradable. Therefore, the use of biodegradable byproducts (starch, cellulose, sodium humate, etc.) as monomers to synthesize environmentally friendly water retainers has gradually attracted widespread attention. This type of natural polymer water retainer has the advantages of wide sources, low production cost, environmental protection and easy degradation. However, compared with synthetic resin water retainers, its water absorption performance is lower and the process is complicated. Therefore, it is necessary to develop environmentally friendly water retainers with simple process, high water retention performance and diversified functions without damaging the environment, which is the development trend of water retainer preparation.

[0003] At present, the research and development of most soil water-retaining agents is mainly aimed at the properties of saline-alkali soils in the north. For example, for most super absorbent hydrogels, the pH value for optimal water retention and nutrient retention is about 7. The pH of red and yellow soils in the south that suffer from seasonal drought is usually in the range of 4-6.5, and they are subject to strong weathering and leaching. The CEC of the soil is low, the fertilizer retention capacity is weak, and the acid and lean problems are prominent. The good water and heat conditions in southern my country are an excellent environment for crop growth, but seasonal drought and the accompanying acid and lean problems are the main factors restricting crop growth. It is urgent to develop environmentally friendly water-retaining agents with high water absorption performance and low cost under acidic conditions to better solve the various problems of seasonal drought, acid and lean in acidic red and yellow soils. Therefore, it is urgently necessary to develop a multifunctional water-retaining agent that is suitable for acidic red and yellow soils and can increase soil pH, CEC, and saturated water content. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a multifunctional water-retaining agent suitable for acidic soil and a preparation method thereof.

[0005] The technical solution of the present invention is: a multifunctional water-retaining agent adapted to acidic soil, which is composed of the following raw materials in parts by weight:

[0006] 9 to 11 parts of chitosan solution with a concentration of 0.019 to 0.021 g / mL, 9 to 11 parts of sodium polyphosphate solution with a mass concentration of 0.5 to 1%, 24 to 25 parts of acrylic acid solution with a neutralization degree of 80 to 85%, 9 to 11 parts of guar gum solution with a concentration of 0.019 to 0.021 g / mL, methylenebisacrylamide accounting for 0.01 to 0.03% of the total dry matter of the chitosan, guar gum and acrylic acid, ammonium persulfate accounting for 0.25 to 0.35% of the total dry matter of the chitosan, guar gum and acrylic acid, and 10 to 12 parts of clay mineral; the clay mineral is selected from one of saponite, montmorillonite and attapulgite.

[0007] Description: The water retaining agent prepared by using the above ingredients can effectively improve the water retention performance of the water retaining agent; there are porous microscopic channels and gaps in the structure of clay minerals, which can absorb and fix water molecules; the addition of chitosan solution can absorb a large amount of water and form a gel structure, and chitosan has good water absorption performance and biological activity, and can also promote plant growth and resist adversity; by compounding clay minerals and chitosan, a material with better water retention performance and stability can be obtained; the composite material promotes the water retaining agent to absorb and retain water more effectively, and releases it to plants or soil during water shortage periods; when the present invention adds clay minerals to the water retaining agent, the water absorption performance of the material can be increased. It can be seen from the experimental results that the present invention adds clay minerals on the basis of preparing the water retaining agent with chitosan to greatly improve the water absorption effect of the water retaining agent, wherein the water absorption effect of saponite>montmorillonite>attapulgite, and the water retention performance of the chitosan water retaining agent without adding clay minerals is increased by 74.4%, 60.9%, and 52.3%, respectively.

[0008] Furthermore, the clay mineral is a clay mineral modified by using 1 to 3 parts of an auxiliary agent, wherein the auxiliary agent comprises, by weight percentage, 5 to 10% of sodium alginate, 5 to 10% of nano-TiO 2 and the balance is a humic acid solution having a mass concentration of 0.05 to 0.1%;

[0009] The modification method is: 2 Fully mix with the sodium alginate, and sieve with a sieve with an aperture of 80 to 100 meshes to obtain composite micropowder; then use a crusher to crush the clay mineral to a particle size of 80 to 100 meshes; divide the clay mineral and the humic acid solution into two equal parts;

[0010] The composite micropowder and one portion of the crushed clay mineral are stirred and mixed, and then added to 1 / 2 of the humic acid solution, the temperature is raised to 70-80°C, and stirred for 10-15 minutes to obtain a mixed suspension A, and the temperature is lowered to room temperature at a rate of 3-5°C / min, and the remaining 1 / 2 of the crushed clay mineral and the remaining 1 / 2 of the humic acid solution are added to the mixed suspension A, and then ultrasonically mixed for 20-25 minutes under the conditions of an ultrasonic frequency of 15-20kHz and an ultrasonic power of 300-400W to obtain a mixed suspension B; the mixed suspension B is dried in a drying chamber at 60-70°C for 30-40 minutes, and ground to 120-140 meshes to obtain a pre-treated clay mineral;

[0011] Description: Humic acid and sodium alginate in the composite additive have good water retention capacity and can improve the water retention of the soil. Adding a small amount of nano-TiO 2 It can improve the water retention performance of clay minerals and also reduce the impact of ultraviolet radiation on water retaining agents and soil due to its good absorption and scattering effects, thereby improving the stability of water retention performance;

[0012] Adding clay minerals and humic acid twice helps to avoid the problem of uneven mixing caused by adding too much material at one time. During the first addition, the composite micropowder and crushed clay minerals are mixed with part of the humic acid solution and stirred at a specific temperature. This process can make the minerals and humic acid initially mixed, and at the same time make the humic acid play its colloidal properties, hydrophilicity and other characteristics, which is conducive to the uniform dispersion and suspension of the minerals; then, by controlling the cooling rate to room temperature, the state of the mixed suspension can be further stabilized. The second addition of the remaining clay minerals and humic acid solution and mixing under ultrasonic conditions can further improve the uniformity and stability of the mixing. The mechanical action and thermal effect of ultrasonic waves can further disperse the particles and improve the uniformity of the mixture; in the preparation method of the composite auxiliary agent of the present invention, the composite micropowder, humic acid solution and clay minerals are fully mixed to effectively enhance the effect of clay minerals on the chitosan water retaining agent, and further improve the performance of the water retaining agent.

[0013] Furthermore, before the composite micropowder is added, the composite micropowder is modified to obtain gelatinized composite micropowder, and the modification method is: the composite micropowder is subjected to microwave treatment for 10 to 12 minutes at a temperature of 50 to 60° C., a microwave power of 270 to 300 W, and normal pressure, and then the temperature is raised to 75 to 80° C., nitrogen is introduced and the pressure is increased to 0.1 to 0.15 MPa, and the pH is adjusted to 7 to 8, and the gelatinized composite micropowder is obtained after stirring for 15 to 20 minutes;

[0014] Description: Sodium alginate and nano-titanium dioxide powders are heated by microwave treatment. In a nitrogen atmosphere, sodium alginate is used as a carbon source to form a carbon nanostructure through a carbonization process. When carbonized sodium alginate and nano-titanium dioxide exist at the same time, a TiO2 with a hierarchical porous structure can be formed between the two. 2 / C nanocomposites, TiO 2 / C nanocomposites can be adsorbed on the surface of clay minerals, thereby expanding the particle gaps of clay minerals and further enhancing the water absorption effect of clay minerals on chitosan water retaining agent.

[0015] Furthermore, the operating parameters of the crusher are: power of 15-20 kW, rotation speed of 200-220 r / min, and crushing time of 50-60 min;

[0016] Note: The above crushing parameters can produce uniform composite additive powder.

[0017] Further, the clay mineral is pre-treated; the pre-treatment method is: spraying 7-8% H2O2 solution in a mass ratio of 1.7-2:1-3 in the clay mineral; 2 O 2 The clay mineral is heated by steam at a temperature of 70 to 85° C. for 3 to 10 minutes; the moisture content of the clay mineral is adjusted to 10 to 15% RH by a dehumidifier;

[0018] Description: Pretreatment of clay minerals can reduce the presence of crystal water and organic matter in clay minerals, making the surface of mineral particles purer, thereby increasing its specific surface area; in addition, steam heating can penetrate into the interior of clay minerals more evenly than ordinary heating methods, thereby achieving a more uniform heating effect, and also helps to reduce the damage to the mineral structure caused by rapid temperature changes; then reduce the water content ratio, reduce the moisture in the mineral, make the mineral particles more compact, increase small gaps and thus increase its specific surface area, and the hydrophilic groups on the surface of clay minerals are more active, which helps to improve its wettability and dispersibility; thereby playing a role in improving the performance of water retaining agents.

[0019] The present invention also provides a method for preparing a multifunctional water-retaining agent suitable for acidic soil, comprising the following steps:

[0020] S1. Preparation

[0021] S1-1, preparation of chitosan solution: weigh chitosan powder according to the concentration and dissolve it in an acidic solution, seal it with a sealing film, ultrasonically treat it at an ultrasonic frequency of 30 to 50 Hz for 3 to 5 minutes, and store it at room temperature for 22 to 26 hours to obtain a chitosan solution with a concentration of 19 to 21 g / mL for later use;

[0022] S1-2, preparation of guar gum solution: weigh guar gum according to the concentration and add it to deionized water at 65-75° C., maintain constant temperature, stir to completely dissolve it into a paste, and set aside;

[0023] S1-3, preparation of acrylic acid solution: taking acrylic acid in a beaker according to the concentration, adding a NaOH solution with a mass concentration of 28-32% at a rate of 3-5 mL / s under ice water bath conditions, stirring and neutralizing to obtain an acrylic acid solution with a neutralization degree of 80-85%, which is set aside;

[0024] S2, Mixed

[0025] The chitosan solution is added to the sodium polyphosphate solution, and the solution is stirred in a constant temperature water bath at 55-65° C. for 25-35 minutes for prepolymerization reaction, and then acrylic acid solution and methylenebisacrylamide are added thereto in sequence, and after stirring at 55-65° C. for 10-20 minutes, the guar gum solution and clay mineral are added to the system, and after the temperature is raised to 65-75° C., ammonium persulfate is continuously added and stirred until gel is generated; nitrogen is continuously introduced during the reaction;

[0026] S3, post-processing

[0027] After the gel is cooled, take it out, rinse it with anhydrous ethanol for 2 to 4 times, and finally dry and crush it for later use, thus obtaining a multifunctional water-retaining agent suitable for acidic soil.

[0028] Furthermore, in step S1-1, the acidic solution is glacial acetic acid with a mass concentration of 9 to 10%;

[0029] Description: Chitosan has good solubility in glacial acetic acid and forms a uniform solution. Compared with other acidic solutions, the chitosan solution formed by chitosan powder dissolved in glacial acetic acid solution has better stability and durability; in addition, chitosan powder dissolved in glacial acetic acid solution can promote the formation of soil aggregates, increase soil organic matter, promote microbial activity and provide nutrient sources to improve soil water retention and fertility in many ways, thereby improving soil quality and promoting plant growth and development.

[0030] Further, in step S3, the drying method is to use a spray drying method for primary drying treatment, and the primary drying time is 10 to 20 minutes; then the temperature is raised to 75 to 85°C at a rate of 10 to 15°C / min, and finally placed in a constant temperature drying oven at 75 to 85°C for secondary drying treatment, and the secondary drying time is 10 to 30 minutes;

[0031] Description: Spray drying has the characteristics of fast heat transfer, rapid water evaporation and short drying time, which can make the gel dry quickly and provide convenience for subsequent crushing and screening.

[0032] Further, in step S3, the crushing parameters are: crushing pressure of 1 to 1.5 MPa, crushing time of 1 to 3 h, crushing temperature of 22 to 26° C., and particle size of 40 to 100 μm;

[0033] Note: The crushing effect is better under the above crushing parameters, and the water retention performance of the prepared multifunctional water-retaining agent is better.

[0034] Further, in step S2, the purity of the nitrogen is 99.99-99.999%;

[0035] Note: Keeping the nitrogen purity within the above range can reduce impurities and prevent explosion.

[0036] The beneficial effects of the present invention are:

[0037] (1) When clay minerals are added to the water retaining agent, the water absorption performance of the material can be increased. The experimental results show that the water retaining agent prepared by the present invention by adding clay minerals to chitosan greatly improves the water absorption effect of the water retaining agent, among which the water absorption effect is saponite>montmorillonite>attapulgite. Compared with the chitosan water retaining agent without adding clay minerals, the water retention performance increases by 74.4%, 60.9% and 52.3%, respectively.

[0038] (2) The chitosan water retainer prepared with the aid of clay minerals in the present invention can not only improve the water absorption and water retention performance of the chitosan water retainer, but also has better water retention effect and stability at high temperature. After 20 days at high temperature, the water retention effect of commercial water retainers and unimproved water retainers on the market is basically reduced to 0, while the water supply capacity of the improved water retainer can be extended by one month; and the water retainer prepared by the present invention is less affected by pH; at the same time, it can reduce the acidity of acidic soil and improve the fertilizer retention capacity of the soil.

[0039] (3) The preparation method of the multifunctional water-retaining agent of the present invention dissolves chitosan in glacial acetic acid solution, which causes less damage to the structure of chitosan than dissolving it in other acidic solutions, and can maintain its high molecular weight, which helps to maintain its durability and improvement effect in the soil; gelatinizing the guar gum solution first can make the guar gum solution form a gelatinized structure, forming a uniformly dispersed mixture colloid, and the stability of the colloid can effectively improve the preparation efficiency of the water-retaining agent, further improve the stability of the water-retaining performance, and thus improve the improvement effect of the water-retaining agent. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a surface structure diagram of the chitosan water-retaining agent under SEM in the present invention;

[0041] Figure 2 This is a surface structure diagram of the soapstone-modified chitosan water-retaining agent under SEM in the present invention;

[0042] Figure 3 This is a surface structure diagram of the montmorillonite-modified chitosan water-retaining agent under SEM in the present invention;

[0043] Figure 4 It is the spectrum of chitosan water-retaining agent, saponite-modified chitosan water-retaining agent and montmorillonite-modified chitosan water-retaining agent under FTIR in the present invention;

[0044] Figure 5 This is a comparison chart of the water retention effects of various water retaining agents after being baked at 40℃ for different times;

[0045] Figure 6 It is the water absorption performance of various water-retaining agents when used repeatedly;

[0046] Figure 7 It is the water absorption performance of various water retaining agents in different pH solutions;

[0047] Figure 8 The water-retaining effect diagrams of the water-retaining agent of the present invention applied to Jiangxi red sand soil (A) are shown;

[0048] Fig. 9 The water retention effect diagram of the water retaining agent of the present invention applied to Anhui red soil (B) is shown;

[0049] Fig.10 The water-retention effect diagrams of the water-retention agent of the present invention applied to Gansu tidal soil (C) are shown. DETAILED DESCRIPTION

[0050] The present invention is further described in detail below in conjunction with specific implementation methods to better reflect the advantages of the present invention.

[0051] Embodiment 1: A multifunctional water-retaining agent adapted to acidic soil, comprising the following raw materials in parts by weight: 10 parts of chitosan solution with a concentration of 0.020 g / mL, 10 parts of sodium polyphosphate solution with a mass concentration of 0.8%, 24 parts of acrylic acid solution with a neutralization degree of 83%, 10 parts of guar gum solution with a concentration of 0.020 g / mL, methylenebisacrylamide accounting for 0.02% of the total dry matter of chitosan, guar gum and acrylic acid, ammonium persulfate accounting for 0.3% of the total dry matter of chitosan, guar gum and acrylic acid, and 11 parts of clay mineral; the clay mineral is selected from saponite;

[0052] The clay mineral is pretreated; the pretreatment method is: according to the mass ratio of clay mineral to hydrogen peroxide solution of 1.8:2, the clay mineral is sprayed with 7.5% H 2 O 2 The solution was heated with steam at 80°C for 5 min. The moisture content of the clay mineral was then adjusted to 13% RH by a dehumidifier.

[0053] The preparation method of the chitosan-based water-retaining agent improved by the clay mineral mentioned above comprises the following steps:

[0054] S1. Preparation

[0055] S1-1, preparation of chitosan solution: chitosan powder is weighed according to the concentration and dissolved in an acidic solution, sealed with a sealing film, ultrasonically treated at an ultrasonic frequency of 40 Hz for 4 minutes, and stored at room temperature for 24 hours to obtain a chitosan solution with a concentration of 20 mg / mL for standby use; in step S1-1, the acidic solution uses glacial acetic acid with a mass concentration of 9.5%;

[0056] S1-2, preparation of guar gum solution: weigh guar gum according to the concentration and add it into deionized water at 70° C., keep the temperature constant, stir to completely dissolve it into a paste, and set aside;

[0057] S1-3, preparation of acrylic acid solution: taking acrylic acid in a beaker according to the concentration, adding a 30% NaOH solution at a rate of 4 mL / s under ice water bath conditions, stirring and neutralizing, obtaining an acrylic acid solution with a neutralization degree of 83%, and setting aside;

[0058] S2, Mixed

[0059] The chitosan solution is added to the sodium polyphosphate solution, and the solution is stirred in a constant temperature water bath at 60°C for 30 minutes for prepolymerization reaction. Then, acrylic acid solution and methylenebisacrylamide are added thereto in sequence. After stirring at 60°C for 15 minutes, the guar gum solution and clay mineral are added to the system. After the temperature is raised to 70°C, ammonium persulfate is continuously added and stirred until gel is generated. Nitrogen is continuously introduced during the reaction. The purity of the nitrogen is 99.995%.

[0060] S3, post-processing

[0061] After the gel is cooled, it is taken out, rinsed with anhydrous ethanol for 3 times, and finally dried and crushed for use to obtain a multifunctional water-retaining agent suitable for acidic soil; in step S3, the drying method is to use a spray drying method for primary drying treatment, and the primary drying time is 15 minutes; then the temperature is raised to 80°C at a rate of 13°C / min, and finally placed in a constant temperature drying oven at 80°C for secondary drying treatment, and the secondary drying time is 20 minutes; the crushing parameters are: crushing pressure is 1.2Mpa, crushing time is 2h, crushing temperature is 24°C, and particle size is 40-100μm.

[0062] Example 2: Different from Example 1, a clay mineral-modified chitosan-based water-retaining agent is composed of the following raw materials in parts by weight: 11 parts of chitosan solution with a concentration of 0.019 g / mL, 11 parts of sodium polyphosphate solution with a mass concentration of 0.5%, 25 parts of acrylic acid solution with a neutralization degree of 80%, 9 parts of guar gum solution with a mass concentration of 0.019 g / mL, methylenebisacrylamide accounting for 0.01% of the total dry matter of the chitosan, guar gum and acrylic acid, ammonium persulfate accounting for 0.25% of the total dry matter of the chitosan, guar gum and acrylic acid, and 10 parts of clay minerals.

[0063] Example 3: Different from Example 1, a clay mineral-modified chitosan-based water-retaining agent is composed of the following raw materials in parts by weight: 9 parts of chitosan solution with a concentration of 0.021 g / mL, 9 parts of sodium polyphosphate solution with a mass concentration of 1%, 24 parts of acrylic acid solution with a neutralization degree of 85%, 11 parts of guar gum solution with a mass concentration of 0.021 g / mL, methylenebisacrylamide accounting for 0.03% of the total dry matter of the chitosan, guar gum and acrylic acid, ammonium persulfate accounting for 0.35% of the total dry matter of the chitosan, guar gum and acrylic acid, and 12 parts of clay minerals.

[0064] Embodiment 4: Different from Embodiment 1, the clay mineral is montmorillonite.

[0065] Embodiment 5: Different from Embodiment 1, the clay mineral is attapulgite.

[0066] Example 6: The pretreatment method is as follows: spraying 7% H2O2 solution in a mass ratio of 1.7:1 in the clay mineral. 2 O 2 The clay mineral was heated with steam at 70°C for 3 min. The water content of the clay mineral was then adjusted to 10% RH by a dehumidifier.

[0067] Example 7: The pretreatment method is as follows: spraying 8% H2O2 solution in a mass ratio of 2:3 in the clay mineral. 2 O 2 The clay mineral was heated with steam at 85°C for 10 min. The moisture content of the clay mineral was then adjusted to 15% RH using a dehumidifier.

[0068] Example 8: The difference from Example 1 is that S1-1, preparation of chitosan solution: chitosan powder is weighed according to the concentration and dissolved in an acidic solution, sealed with a sealing film, ultrasonically treated at an ultrasonic frequency of 30 Hz for 5 min, and stored at room temperature for 22 h to obtain a chitosan solution with a concentration of 19 g / mL for use.

[0069] Example 9: The difference from Example 1 is that S1-1, preparation of chitosan solution: chitosan powder is weighed according to the concentration and dissolved in an acidic solution, sealed with a sealing film, ultrasonically treated at an ultrasonic frequency of 50 Hz for 3 min, and stored at room temperature for 26 h to obtain a chitosan solution with a concentration of 21 g / mL for use.

[0070] Example 10: The difference from Example 1 is that S1-3, preparation of acrylic acid solution: acrylic acid is measured in a beaker according to the concentration, and a NaOH solution with a mass concentration of 28% is added dropwise at a rate of 3 mL / s under ice-water bath conditions, and stirred for neutralization to obtain an acrylic acid solution with a neutralization degree of 80%, which is set aside.

[0071] Example 11: The difference from Example 1 is that S1-3, preparation of acrylic acid solution: acrylic acid is measured in a beaker according to the concentration, and a NaOH solution with a mass concentration of 32% is added dropwise at a rate of 5 mL / s under ice-water bath conditions, and stirred for neutralization to obtain an acrylic acid solution with a neutralization degree of 85%, which is set aside.

[0072] Example 12: Different from Example 1, in step S2, the chitosan solution is added to the sodium polyphosphate solution, stirred in a constant temperature water bath at 55°C for 35 minutes for prepolymerization reaction, and then acrylic acid solution and methylenebisacrylamide are added thereto in sequence. After stirring at 55°C for 20 minutes, the guar gum solution and clay mineral are added to the system, and after heating to 65°C, ammonium persulfate is continued to be added and stirred until gel is produced.

[0073] Example 13: Different from Example 1, in step S2, the chitosan solution is added to the sodium polyphosphate solution, stirred in a constant temperature water bath at 65°C for 25 minutes for prepolymerization reaction, and then acrylic acid solution and methylenebisacrylamide are added thereto in sequence. After stirring at 65°C for 10 minutes, the guar gum solution and clay mineral are added to the system, and after heating to 75°C, ammonium persulfate is continued to be added and stirred until gel is produced.

[0074] Example 14: Different from Example 1, in step S3, the drying method is to use spray drying method for the initial drying treatment, and the initial drying time is 10 minutes; then the temperature is raised to 75°C at a rate of 10°C / min, and finally placed in a constant temperature drying oven at 75°C for secondary drying treatment, and the secondary drying time is 10 minutes.

[0075] Example 15: Different from Example 1, in step S3, the drying method is to use spray drying method for the initial drying treatment, and the initial drying time is 20 minutes; then the temperature is raised to 85°C at a rate of 15°C / min, and finally placed in a constant temperature drying oven at 85°C for secondary drying treatment, and the secondary drying time is 30 minutes.

[0076] Example 16: Different from Example 1, in step S3, the crushing parameters are: crushing pressure is 1 MPa, crushing time is 1 h, crushing temperature is 22°C, and particle size is 40-100 μm.

[0077] Example 17: Different from Example 1, in step S3, the crushing parameters are: crushing pressure is 1.5 MPa, crushing time is 3 h, crushing temperature is 26°C, and particle size is 40-100 μm.

[0078] Example 18: Different from Example 1, the clay mineral is a clay mineral modified by using 2 parts of additives, and the additives are calculated by mass percentage, including: 8% sodium alginate, 8% nano-TiO 2 and the balance is a humic acid solution having a mass concentration of 0.07%;

[0079] The modification method is: nano-TiO 2 Mix with sodium alginate, sieve with a sieve with an aperture of 80-100 meshes to obtain composite micropowder; then use a crusher to crush the clay mineral to a particle size of 80-100 meshes; divide the clay mineral and humic acid solution into 2 equal parts, and the working parameters of the crusher are: power 18kw, speed 210r / min, crushing time 55min;

[0080] The composite micropowder and one portion of the crushed clay mineral were stirred and mixed, and then added to 1 / 2 of the humic acid solution, heated to 75°C, stirred for 12 minutes to obtain a mixed suspension A, cooled to room temperature at a rate of 4°C / min, and then the remaining 1 / 2 of the crushed clay mineral and the remaining 1 / 2 of the humic acid solution were added to the mixed suspension A, and then ultrasonically mixed for 23 minutes under the conditions of an ultrasonic frequency of 18kHz and an ultrasonic power of 350W to obtain a mixed suspension B; the mixed suspension B was dried in a drying chamber at 65°C for 35 minutes, and ground to a particle size of 120-140 meshes to obtain a modified clay mineral;

[0081] The composite micropowder is modified to obtain gelatinized composite micropowder. The modification method is as follows: the composite micropowder is subjected to microwave treatment for 11 minutes at a temperature of 55°C, a microwave power of 285W, and normal pressure, and then the temperature is raised to 78°C, nitrogen is introduced and the pressure is increased to 0.13MPa, and the pH is adjusted to 7.5, and the gelatinized composite micropowder is obtained after stirring for 18 minutes.

[0082] Example 19: Different from Example 18, the clay mineral is a clay mineral modified by using 1 part of an additive, and the additive comprises, by mass percentage, 5% sodium alginate, 5% nano-TiO 2and the balance is a humic acid solution with a mass concentration of 0.05%.

[0083] Example 20: Different from Example 18, the clay mineral is a clay mineral modified by using 3 parts of additives, and the additives are calculated by mass percentage, including: 10% sodium alginate, 10% nano-TiO 2 and the balance is a humic acid solution with a mass concentration of 0.1%.

[0084] Example 21: Different from Example 18, the modification method is: adding nano-TiO 2 The mixture was fully mixed with sodium alginate and sieved with a sieve with an aperture of 80 to 100 meshes to obtain a composite micropowder; the clay mineral was then crushed with a crusher to a particle size of 80 to 100 meshes; the clay mineral and the humic acid solution were divided into two equal parts, the composite micropowder and one of the crushed clay minerals were stirred and mixed, and then added to 1 / 2 of the humic acid solution, heated to 70°C, stirred for 15 minutes to obtain a mixed suspension A, cooled to room temperature at a rate of 3°C / min, and then the remaining 1 / 2 of the crushed clay mineral and the remaining 1 / 2 of the humic acid solution were added to the mixed suspension A, and then ultrasonically mixed for 25 minutes under the conditions of an ultrasonic frequency of 15kHz and an ultrasonic power of 300W to obtain a mixed suspension B; the mixed suspension B was dried in a drying chamber at 60°C for 40 minutes, and ground to a particle size of 120 to 140 meshes to obtain the modified clay mineral.

[0085] Example 22: Different from Example 18, the modification method is: adding nano-TiO 2 The mixture was fully mixed with sodium alginate and sieved with a sieve with an aperture of 80-100 meshes to obtain composite micropowder; the clay mineral was then crushed with a crusher to a particle size of 80-100 meshes; the clay mineral and humic acid solution were divided into two equal parts,

[0086] The composite micropowder and one portion of the crushed clay mineral were stirred and mixed, and then added to 1 / 2 of the humic acid solution, heated to 80°C, stirred for 10 minutes to obtain a mixed suspension A, cooled to room temperature at a rate of 5°C / min, and then the remaining 1 / 2 of the crushed clay mineral and the remaining 1 / 2 of the humic acid solution were added to the mixed suspension A, and then ultrasonically mixed for 20 minutes under the conditions of an ultrasonic frequency of 20kHz and an ultrasonic power of 400W to obtain a mixed suspension B; the mixed suspension B was dried in a drying chamber at 70°C for 30 minutes, and ground to a particle size of 120-140 meshes to obtain the modified clay mineral.

[0087] Example 23: Different from Example 18, the operating parameters of the crusher are: power is 15kw, speed is 200r / min, and crushing time is 60min.

[0088] Example 24: Different from Example 18, the operating parameters of the crusher are: power of 20kw, rotation speed of 220r / min, and crushing time of 50min.

[0089] Example 25: Different from Example 18, the composite micropowder is modified before being added to obtain gelatinized composite micropowder. The modification method is as follows: the composite micropowder is microwave-treated for 12 minutes at a temperature of 50°C, a microwave power of 270 W, and normal pressure, and then the temperature is raised to 75°C, nitrogen is introduced and the pressure is increased to 0.1 MPa, and the pH is adjusted to 7. After stirring for 15 minutes, gelatinized composite micropowder is obtained.

[0090] Example 26: Different from Example 18, the composite micropowder is modified before being added to obtain gelatinized composite micropowder. The modification method is as follows: the composite micropowder is microwave-treated at a temperature of 60°C, a microwave power of 300 W, and normal pressure for 10 minutes, then the temperature is raised to 80°C, nitrogen is introduced and the pressure is increased to 0.15 MPa, and the pH is adjusted to 8. After stirring for 20 minutes, gelatinized composite micropowder is obtained.

[0091] Comparison Example

[0092] Comparative Example 1: Different from Example 1, no clay mineral is added to the composite additive.

[0093] Comparative Example 2: Different from Example 1, the clay mineral is not pre-treated.

[0094] Control Example 3: Different from Example 18, the preparation method of the auxiliary agent is to directly mix the ingredients.

[0095] Control Example 4: The difference from Example 1 is that S1-3, preparation of acrylic acid solution: acrylic acid is measured in a beaker according to the proportion, and a NaOH solution with a mass concentration of 30% is added dropwise at a rate of 4 mL / s under ice-water bath conditions, and stirred for neutralization to obtain an acrylic acid solution with a neutralization degree of 90%, which is set aside.

[0096] Comparative Example 5: Different from Example 1, in step S3, the material is dried in a constant temperature drying oven at 80°C for 20 minutes.

[0097] Control Example 6: Different from Example 1, in step S3, anhydrous ethanol is not used to rinse the gel.

[0098] Experimental example:

[0099] 1. Analysis of attached figures

[0100] The morphology of the synthesized water-retaining agent was analyzed by scanning electron microscopy (SEM) at 5000 times magnification. Figures 1 to 3As shown. The results show that the surface of the chitosan water retainer is uneven, and the addition of clay minerals causes more particles and wrinkles to appear on the surface of the water retainer, increasing the specific surface area of ​​the water retainer, expanding the network space of the water retainer cross-linked gel, and providing active water absorption points for more water. At the same time, more pore structures appear on the surface, providing channels for water molecules to enter the water retainer network structure. The two work together to significantly improve the water absorption effect of the water retainer;

[0101] The infrared spectrum analysis results of synthetic water retaining agent are as follows Figure 4 As shown. FTIR spectrum at 3377cm -1 The broad peak at 2926 cm-1 is attributed to the OH stretching vibration. -1 The peak at 2 – C dynamic peak, at 1564cm -1 The N–H absorption vibration peak appears at 1454 cm -1 -CH 2 The absorption vibration peak of 3377cm -1 The peak at 3397 cm -1 、3382cm -1 It shows that O–H forms new bonds with Al, Fe, etc., indicating that saponite and montmorillonite participate in the reaction of water retaining agent synthesis.

[0102] Depend on Figure 5 It can be seen that the water-retaining agent prepared by this method has better water absorption effect than commercial water-retaining agents on the market. After 20 days, the water-retaining effect of commercial water-retaining agents on the market and unmodified water-retaining agents basically dropped to 0, while the improved water-retaining agent still retained 30-40% of water after one month of high temperature.

[0103] Depend on Figure 6 It can be seen that when the water-retaining agent absorbs water, is dried, and then absorbs water again, and its effect of multiple uses is measured, the water absorption effect of the improved water-retaining agent is better than that of commercial water-retaining agents and unimproved water-retaining agents when used for the first and second time, but its effect gradually decreases with the increase in the number of uses, and the water absorption effect is completely lost when it is used for the fourth time.

[0104] Depend on Figure 7It can be seen that in the range of pH = 3 to 8, pH value has no significant correlation effect on the water absorption performance of commercial and chitosan water retainers (r = -0.02, P = 0.98; r = -0.50, P = 0.11), while saponite and montmorillonite water retainers maintain good water retention performance between pH = 4 and 7. When the solution pH = 3 or 8, the water absorption performance of the water retainers shows a downward trend, indicating that the improved water retainers have a certain stability for the pH change from acidic to neutral in the solution environment, and are very suitable for acidic to neutral soils. Under extremely strong acidic conditions, the protonation of carboxylate anions on the surface of the water retainer reduces the repulsive force between anions, so further cross-linking of the hydrogel network will limit its swelling capacity; under alkaline conditions, excess cations weaken the electrostatic repulsive interaction by shielding the charge of carboxylate anions. At the same time, the water absorption performance of the water retaining agent in the electrolyte solution is significantly reduced. The reason is that in a salty environment, the negative charge of the water retaining agent is shielded by the salt cations, resulting in a decrease in the mutual repulsion. Figure 7 It can be found that in electrolyte solution, montmorillonite water-retaining agent has the best effect, which may be related to the high negative charge of montmorillonite and its high buffering performance.

[0105] For the water-retaining agents prepared in Examples 1 to 26 and Comparative Examples 1 to 6, 5 g of the water-retaining agents were weighed and placed in a nylon mesh bag. The bag was immersed in distilled water until water absorption equilibrium was reached. The excess distilled water was slowly poured out. Two cubes of water-retaining agents with a side length of 1 cm were separated by a cotton thread. Each two water-retaining agents were grouped together. The mass m of the cube water-retaining agent that absorbed enough water was weighed. 1 The average dry matter mass is m 2 According to the formula R = (m 1 -m 2 ) / m 2 , calculate the water retention effect of water retaining agent under different preparation methods;

[0106] 2. Explore the effects of clay mineral addition, additive addition and additive preparation method on the water retention performance of water retaining agent

[0107] Table 1 Performance measurement of water-retaining agents prepared in Examples 1 to 15 and Comparative Examples 1 to 4

[0108]

[0109] Conclusion: It can be seen from Examples 1 and 4 to 5 that the effect of clay minerals on improving water retention is saponite>montmorillonite>attapulgite; in Control Example 1, no clay minerals were added, and the water retention effect was significantly lower than that of Examples 1 and 4 to 5; therefore, it can be concluded that the addition of clay minerals to the water retaining agent in the present invention can effectively improve the water retention effect of the water retaining agent;

[0110] Comparison of the data of Examples 1, 6 to 7 and Control Example 2 shows that the lack of pretreatment of the clay mineral in Control Example 2 results in a lower water retention performance of the water retaining agent prepared in Control Example 3. This is mainly because the addition of hydrogen peroxide solution and heating can effectively reduce the crystal water and organic matter in the clay mineral, making the surface of the mineral particles purer, thereby increasing its specific surface area, further enhancing the effect of the clay mineral on the chitosan water retaining agent, and thus improving the water retention performance of the water retaining agent; the comparison of Examples 1, 2 to 5 and 18 to 26 shows that the water retaining agent prepared in Control Example 3 has a lower water retention performance. This is mainly because the addition of hydrogen peroxide solution and heating can effectively reduce the crystal water and organic matter in the clay mineral, making the surface of the mineral particles purer, thereby increasing its specific surface area, and further enhancing the effect of the clay mineral on the chitosan water retaining agent, thereby improving the water retention performance of the water retaining agent. It can be seen that the water-retention effect of the water-retaining agent is significantly improved after the clay mineral is modified by the auxiliary agent and added to the water-retaining agent. Example 18 is the optimal state. From the comparison of Example 18, Example 21 to Example 22 and Control Example 3, it can be seen that the water-retaining effect of Control Example 3 is significantly lower. This is because the use of this method to add clay minerals and humic acid twice helps to avoid the problem of uneven mixing or excessive local concentration caused by adding too much material at one time, which is more conducive to improving the effect of clay minerals on the chitosan water-retaining agent and further improving the water-retaining performance of the water-retaining agent.

[0111] 3. Investigate the effect of acrylic acid neutralization degree on the performance of water retention agent

[0112] Table 2 Performance measurement of water-retaining agents prepared in Example 1, Examples 10-11 and Comparative Example 4

[0113]

[0114] Conclusion: From the data comparison of Example 1, Examples 10-11 and Control Example 4, it can be seen that with the increase of the percentage of neutralization degree of acrylic acid, the water absorption performance of the water-retaining agent improved by saponite and montmorillonite first increases and then decreases. At 85% and 80%, the water absorption effect is the best, reaching 833.0g / g and 866.5g / g respectively. When the neutralization degree reaches 90%, the water absorption effect of the water-retaining agent decreases significantly, decreasing by 35.4% and 58.2%. This is mainly because when NaOH partially neutralizes acrylic acid, NaOH converts the -COOH group into -COO-Na + , where —COO fixed on the molecular chain - The molecular network structure expands through electrostatic repulsion. To maintain electrical neutrality, Na + The concentration difference is formed inside and outside the resin network, which generates osmotic pressure and allows water molecules to penetrate, thereby absorbing a large amount of water. However, as the degree of neutralization increases, the adjacent COO - The repulsive force between them increases, the hydrogen bonding force between water molecules and ions and the repulsive force between adjacent hydrogen bonds increase, resulting in the inhibition of the expansion of the water retaining agent molecular network, resulting in a decrease in the reaction rate and a decrease in water absorption performance.

[0115] 4. Explore the effect of water retaining agent preparation temperature on water retaining agent performance

[0116] Table 3 Performance measurement of water-retaining agents prepared in Example 1, Examples 8-9, 12-17 and Comparative Examples 5-6

[0117]

[0118]

[0119] Conclusion: From the data of Example 1, Example 14 to Example 15 and Control Example 6 in Table 3, it can be seen that the drying effect of the water-retaining agent prepared by the temperature-increasing drying method in Control Example 6 cannot ensure uniform heating inside and outside of the gel, reduce the thermal stress caused by the temperature difference, thereby making the stability of the water-retaining performance worse, resulting in a significant decrease in the water-retaining effect in Control Example 6; and in Control Example 5, due to the lack of anhydrous ethanol immersion operation, the specific surface area and adsorption capacity are both reduced, resulting in a worse improvement effect of the water-retaining agent.

[0120] 5. Application effect of water retaining agent in Jiangxi red sandy soil (A), Anhui red soil (B), Gansu fluvo-aquic soil (C)

[0121] The wilting coefficient refers to the soil moisture content when the plant begins to wilt permanently. It is worth noting that the wilting coefficients vary greatly between different soils. For wheat, a soil moisture content higher than 10% can prevent wheat from permanently wilting. Therefore, we took wheat as an example to analyze the effects of different water retaining agents on the wilting situation when the soil moisture content dropped to 10%.

[0122] Soil from the surface layer (0-20cm) of farmland in Anhui red soil, Jiangxi red sandy soil and Gansu tidal soil was collected respectively, and the fresh soil was air-dried and ground through a 60-mesh sieve. 100g of soil samples were weighed and placed in 4 bottom-drilled plastic cups respectively, and two groups were set up in parallel. At the same time, 0.15g of chitosan water-retaining agent, saponite-modified water-retaining agent, montmorillonite-modified water-retaining agent, and commercially available water-retaining agent were weighed at an addition amount of 0.15%. They were applied to the soil samples respectively and stirred, and a group of single soil without any water-retaining agent was set up at the same time. After a 300-mesh filter was placed at the bottom of the plastic cup, sufficient deionized water was added for leaching. After the soil samples reached saturated water content, all soil samples were placed in a 40°C constant temperature incubator for culture. At the same time, use a soil sampler to collect soil at 12h, 24h, 36h, 48h, 60h, 72h, and 96h, place it in a plastic cup, and weigh the net weight of the plastic cup and the weight after adding the soil sample, and record them as m0 and m1 respectively. Then put the collected soil into an 80℃ oven, wait until the moisture is completely dried, and weigh it and record it as m 2 The calculation formula for soil moisture content in each period is:

[0123] Depend on Figure 8 , Fig. 9 , Fig.10 It can be seen that the application of water retaining agent can significantly increase the saturated water content of soil, and the drought resistance of soil with improved water retaining agent (saponite, montmorillonite) is higher than that of soil with chitosan water retaining agent and commercial water retaining agent. Under extremely high temperature (40℃) conditions, the water content of red sand soil alone, after adding commercial water retaining agent, chitosan water retaining agent, saponite improved water retaining agent and montmorillonite improved water retaining agent, dropped to 10% after 37.2h, 68.9h, 93.7h, 102.5h and 124.7h respectively. The improvement of saponite and montmorillonite extended the water retention time of chitosan water retaining agent by 9.3% and 33.1% respectively. Under extremely high temperature (40℃) conditions, the water content of red soil dropped to 10% after 29.3h, 52.4h, 61.7h, 100.1h and 99.6h of adding commercial water retainer, chitosan water retainer, saponite water retainer and montmorillonite water retainer respectively. The water retention time of chitosan water retainer was extended by 62.2% and 61.4% by saponite and montmorillonite respectively. Under extremely high temperature (40℃) conditions, the water content of fluvo-aquic soil dropped to 10% after 30.1h, 38.3h, 40.4h, 50.7h and 54.6h of adding commercial water retainer, chitosan water retainer, saponite water retainer and montmorillonite water retainer respectively. The water retention time of chitosan water retainer was extended by 25.5% and 35.1% by saponite and montmorillonite respectively. This is mainly due to the presence of hydrophilic functional groups in the water retainer. The highly cross-linked water retainer has strong adsorption and complexing capabilities, allowing water to easily enter the internal polymer network and form a water barrier with soil particles. This process prevents the evaporation of water on the soil surface, thereby improving the soil's water retention capacity. Adding saponite and montmorillonite can significantly enhance the role of chitosan water retainer in alleviating soil drought.

[0124] 6. Effects of water retaining agents on pH and CEC of Jiangxi red sandy soil (A), Anhui red soil (B), and Gansu fluvo-aquic soil (C)

[0125] After the above-mentioned cultivation experiment, the soil samples after adding the water retaining agent were air-dried and ground to measure the basic properties of the soil. The soil pH value was measured using a pH meter (Orion 3Star, Thermo Electron, USA) at a soil-water ratio of 1:2.5 (w:v), and the soil CEC was measured using the ammonium acetate method. The results are shown in the following table:

[0126] Table 4 Effect of water retaining agent on pH and CEC of various soils

[0127]

[0128] Studies have shown that the water retainer prepared by this method can improve the basic properties of the soil after application. As shown in Table 4, compared with the control soil without water retainer, the pH of the soil with water retainer applied has increased significantly, especially in acidic soil, which may be related to the higher alkalinity of the water retainer. The alkalinity of the water retainer was determined to be 6.89 mol / kg for commercial water retainer; 5.73 mol / kg for control chitosan water retainer; 5.31 mol / kg for chitosan water retainer modified by saponite, and 4.24 mol / kg for chitosan water retainer modified by montmorillonite. At the same time, the application of the water retainer prepared by this scheme also significantly improves the CEC of the soil. The reason is that the water retainer contains a large amount of organic matter, and its surface has a large number of organic functional groups, such as carboxyl, hydroxyl, amide, etc. These functional groups carry a large amount of negative charge, and applying them to the soil promotes the increase of soil CEC. Therefore, the chitosan water retainer synthesized by the present invention can not only alleviate the degree of soil drought, but also has a certain effect of improving the acidity of acidic soil and improving fertilizer conservation.

Claims

1. A multifunctional water-retaining agent suitable for acidic soil. It is characterized in that It is composed of the following raw materials in parts by weight: 9 to 11 parts of chitosan solution with a concentration of 0.019 to 0.021 g / mL, 9 to 11 parts of sodium polyphosphate solution with a mass concentration of 0.5 to 1%, 24 to 25 parts of acrylic acid solution with a neutralization degree of 80 to 85%, 9 to 11 parts of guar gum solution with a concentration of 0.019 to 0.021 g / mL, methylenebisacrylamide accounting for 0.01 to 0.03% of the total dry matter weight of the chitosan, guar gum and acrylic acid, ammonium persulfate accounting for 0.25 to 0.35% of the total dry matter weight of the chitosan, guar gum and acrylic acid, and 10 to 12 parts of clay mineral; the clay mineral is selected from one of saponite, montmorillonite and attapulgite.

2. A multifunctional water-retaining agent adapted to acidic soil according to claim 1, It is characterized in that The clay mineral is a clay mineral modified by using 1 to 3 parts of an auxiliary agent, wherein the auxiliary agent comprises, by weight percentage, 5 to 10% of sodium alginate, 5 to 10% of nano-TiO 2 and the balance is a humic acid solution having a mass concentration of 0.05 to 0.1%; The modification method is: 2 Fully mix with the sodium alginate, and sieve with a sieve with an aperture of 80 to 100 meshes to obtain composite micropowder; then use a crusher to crush the clay mineral to a particle size of 80 to 100 meshes; divide the clay mineral and the humic acid solution into two equal parts; The composite micropowder and one portion of the crushed clay mineral are stirred and mixed, then added to 1 / 2 of the humic acid solution, heated to 70-80°C, stirred for 10-15 minutes to obtain a mixed suspension A, cooled to room temperature at a rate of 3-5°C / min, and then the remaining 1 / 2 of the crushed clay mineral and the remaining 1 / 2 of the humic acid solution are added to the mixed suspension A, and then ultrasonically mixed for 20-25 minutes under the conditions of an ultrasonic frequency of 15-20kHz and an ultrasonic power of 300-400W to obtain a mixed suspension B; the mixed suspension B is dried in a drying chamber at 60-70°C for 30-40 minutes, and ground to a particle size of 120-140 meshes to obtain a modified clay mineral.

3. A multifunctional water-retaining agent adapted to acidic soil according to claim 2, It is characterized in that The composite micropowder is modified before being added to obtain gelatinized composite micropowder, and the modification method is as follows: the composite micropowder is subjected to microwave treatment for 10 to 12 minutes at a temperature of 50 to 60° C., a microwave power of 270 to 300 W, and normal pressure, and then the temperature is raised to 75 to 80° C., nitrogen is introduced and the pressure is increased to 0.1 to 0.15 MPa, the pH is adjusted to 7 to 8, and the gelatinized composite micropowder is obtained after stirring for 15 to 20 minutes.

4. A multifunctional water-retaining agent adapted to acidic soil according to claim 2, It is characterized in that The working parameters of the crusher are: power of 15-20kw, rotation speed of 200-220r / min, and crushing time of 50-60min.

5. A multifunctional water-retaining agent adapted to acidic soil according to claim 1, It is characterized in that The clay mineral is pretreated; the pretreatment method is: spraying 7-8% H2O2 solution in the clay mineral according to the mass ratio of clay mineral to hydrogen peroxide solution of 1.7-2:1-3; 2 O 2 The clay mineral is heated by steam at a temperature of 70 to 85° C. for 3 to 10 minutes; and the moisture content of the clay mineral is adjusted to 10 to 15% RH by a dehumidifier.

6. A method for preparing a multifunctional water-retaining agent adapted to acidic soil, which is used to prepare a multifunctional water-retaining agent adapted to acidic soil according to any one of claims 1 to 5. It is characterized in that The following steps are involved: S1. Preparation S1-1, preparation of chitosan solution: weigh chitosan powder according to the concentration and dissolve it in an acidic solution, seal it with a sealing film, ultrasonically treat it at an ultrasonic frequency of 30 to 50 Hz for 3 to 5 minutes, and store it at room temperature for 22 to 26 hours to obtain a chitosan solution with a concentration of 19 to 21 g / mL for later use; S1-2, preparation of guar gum solution: weigh guar gum according to the concentration and add it to deionized water at 65-75° C., maintain constant temperature, stir to completely dissolve it into a paste, and set aside; S1-3, preparation of acrylic acid solution: taking acrylic acid in a beaker according to the concentration, adding a NaOH solution with a mass concentration of 28-32% at a rate of 3-5 mL / s under ice water bath conditions, stirring and neutralizing to obtain an acrylic acid solution with a neutralization degree of 80-85%, which is set aside; S2, Mixed The chitosan solution is added to the sodium polyphosphate solution, and the solution is stirred in a constant temperature water bath at 55-65° C. for 25-35 minutes for prepolymerization reaction, and then acrylic acid solution and methylenebisacrylamide are added thereto in sequence, and after stirring at 55-65° C. for 10-20 minutes, the guar gum solution and clay mineral are added to the system, and after the temperature is raised to 65-75° C., ammonium persulfate is continuously added and stirred until gel is generated; nitrogen is continuously introduced during the reaction; S3, post-processing After the gel is cooled, take it out, rinse it with anhydrous ethanol for 2 to 4 times, and finally dry and crush it for later use to obtain a multifunctional water-retaining agent suitable for acidic soil.

7. The method for preparing a multifunctional water-retaining agent adapted to acidic soil according to claim 6, It is characterized in that In step S1-1, the acidic solution is glacial acetic acid with a mass concentration of 9-10%.

8. The method for preparing a multifunctional water-retaining agent adapted to acidic soil according to claim 5, It is characterized in that In step S3, the drying method is to use spray drying method for primary drying treatment, and the primary drying time is 10 to 20 minutes; then the temperature is increased to 75 to 85°C at a rate of 10 to 15°C / min, and finally placed in a constant temperature drying oven at 75 to 85°C for secondary drying treatment, and the secondary drying time is 10 to 30 minutes.

9. The method for preparing a multifunctional water-retaining agent adapted to acidic soil according to claim 6, It is characterized in that In step S3, the crushing parameters are: crushing pressure of 1-1.5 MPa, crushing time of 1-3 h, crushing temperature of 22-26° C., and particle size of 40-100 μm.

10. The method for preparing a multifunctional water-retaining agent adapted to acidic soil according to claim 6, It is characterized in that In step S2, the purity of the nitrogen is 99.99-99.999%.

Citation Information

Patent Citations

  • Method for preparing water-loss reducer by copolymerizing acrylic acid, humic acid and attapulgite

    CN101104667A

  • Agricultural water retaining agent and preparation method thereof

    CN108383945A

  • Preparation method of drought-resistant water-retaining agent

    CN108559516A

  • Manufacturing method and application of montmorillonite with low iron oxide content

    CN117446815A

  • Water-absorbent material

    JP2002037822A

Cited By

  • Multifunctional farmland water-retaining agent as well as preparation method and use method thereof

    CN119751760A

  • Water-retaining agent as well as preparation method and application thereof

    CN120157815A

  • A water retention agent, its preparation method and application

    CN120157815B

  • Method for improving survival rate of young poplar man-made forest in sandy and arid region and soil quality of forest land based on mycorrhizal symbiosis

    CN120642719A

  • Soil conditioner capable of increasing content of organic matters and preparation method of soil conditioner

    CN121427536A